2007
DOI: 10.1016/j.pbi.2007.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Networks of WRKY transcription factors in defense signaling

Abstract: Members of the complex family of WRKY transcription factors have been implicated in the regulation of transcriptional reprogramming associated with plant immune responses. Recently genetic evidence directly proving their significance as positive and negative regulators of disease resistance has accumulated. WRKY genes were shown to be functionally connected forming a transcriptional network composed of positive and negative feedback loops and feed-forward modules. Within a web of partially redundant elements s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
909
1
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,158 publications
(935 citation statements)
references
References 47 publications
(43 reference statements)
17
909
1
8
Order By: Relevance
“…The WRKY TF superfamily consists of 74 and 109 members in Arabidopsis (Arabidopsis thaliana) and rice (Oryza sativa), respectively (Eulgem and Somssich, 2007;Ross et al, 2007). Members of this family contain at least one conserved DNA-binding region, designated the WRKY domain, comprising the highly conserved WRKYGQK peptide sequence and a zinc finger motif (CX 4-7 CX 22-23 HXH/C).…”
Section: The Wrky Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The WRKY TF superfamily consists of 74 and 109 members in Arabidopsis (Arabidopsis thaliana) and rice (Oryza sativa), respectively (Eulgem and Somssich, 2007;Ross et al, 2007). Members of this family contain at least one conserved DNA-binding region, designated the WRKY domain, comprising the highly conserved WRKYGQK peptide sequence and a zinc finger motif (CX 4-7 CX 22-23 HXH/C).…”
Section: The Wrky Factorsmentioning
confidence: 99%
“…Phylogenetic sequence analysis and comparative transcriptomics have revealed that they have retained their functions between monocots and dicots (Mangelsen et al, 2008). The majority of the analyzed WRKY genes respond to pathogen attack and to the endogenous signal molecule salicylic acid (SA; Eulgem and Somssich, 2007).…”
Section: The Wrky Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…WRKY TFs play pivotal roles in the complex signaling mediating plant responses to biotic and abiotic stresses (Ulker and Somssich 2004;Eulgem and Somssich 2007; Abstract OsWRKY47 is a divergent rice transcription factor belonging to the group II of the WRKY family. A transcriptomic analysis of the drought response of transgenic rice plants expressing P SARK ::IPT, validated by qPCR, indicated that OsWRKY47 expression was induced under drought stress in P SARK ::IPT plants.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] They have been investigated extensively for their possible involvement in defense responses against attack by pathogens, mainly in dicotyledonous plants. 7,8) The rice genome is predicted to contain over 100 WRKY (OsWRKY) genes.…”
mentioning
confidence: 99%